Aggregation and stability of sulfate-modified polystyrene nanoplastics in synthetic and natural waters. (1st January 2021) - Wang, Junyu; Zhao, Xiaoli; Wu, Aiming; Tang, Zhi; Niu, Lin; Wu, Fengchang; Wang, Fanfan; Zhao, Tianhui; Fu, Zhiyou
Abstract: Nanoplastics (NPs) are becoming emerging pollutants of global concern. Understanding the environmental behavior of NPs is crucial for their environmental and human risk assessment. In this study, the aggregation and stability of polystyrene (PS) NPs were investigated under different hydrochemical conditions such as pH, salt type (NaCl, CaCl2, Na2 SO4 ), ionic strength (IS), and natural organic matter (NOM). The critical coagulation concentrations of PS NPs were determined to be 158.7 mM NaCl, 12.2 mM CaCl2, and 80.0 mM Na2 SO4 . Ca 2+ was more effective in destabilizing PS NPs, compared to Na +, owing to its stronger charge screening effect. In the presence of monovalent ions, NOM reduced aggregation through steric repulsion, whereas in the case of divalent ions, NOM induced aggregation through cation bridging. Initial and long-term stability studies demonstrated that, in waters with high IS and NOM content, NOM was the most significant factor affecting NPs aggregation. PS NPs would be highly suspended in all freshwaters, and even in wastewater, whereas they would aggregate rapidly and deposit in seawater. Finally, a statistical model was established to evaluate the hydrodynamic diameter of NPs in different waters. The results indicated the stability of PS NPs in natural aquatic environments and their potential for long-term transport. Graphical abstract: Image 1 Highlights: Electrostatic interactions and steric repulsions dominate the stability of polystyrene nanoplastics. NOM plays a major role on nanoplastics aggregation in waters with high ionic strength and NOM content. Polystyrene nanoplastics were suspended in freshwaters and wastewater; whereas they aggregated and deposited in seawater. A statistical model for the quantitative evaluation of nanoplastics aggregation was established. Abstract : Capsule: PS NPs aggregation was dominated by electrostatic interactions and steric repulsions. PS NPs were highly suspended in freshwaters and wastewater other than in the seawater.